Ingenol mebutate in actinic keratosis: a clinical, videodermoscopic and immunohistochemical study. (25th July 2016) - Bobyr, I.; Campanati, A.; Consales, V.; Martina, E.; Molinelli, E.; Diotallevi, F.; Brisigotti, V.; Giangiacomi, M.; Ganzetti, G.; Giuliodori, K.; Offidani, A.
Abstract: Background: Actinic keratosis (AK) is a cutaneous intraepithelial neoplasm that typically develops on sun‐damaged skin. The incidence of AK is increasing worldwide, and it is accepted as the most frequent pre‐malignant lesion in humans. Objectives: To demonstrate that ingenol mebutate gel is effective in the treatment of actinic keratoses because of its clinical, dermoscopic, capillaroscopic, histopathological and immunohistochemical treatment outcomes. Methods: Sixty individuals with multiple non‐hypertrophic AKs were enrolled into this non‐randomized, open‐label, prospective, trial. Acquisition of clinical, dermoscopic and capillaroscopic images at baseline (T0), immediately after treatment on 3 rd (trunk and/or extremities) or 4 th (scalp and/or face) day (T1), 14 days after the end of the treatment (T2) and at 60 days (T3). A subgroup of 20 patients received a cutaneous biopsy both at baseline and at T3 for histological and immunohistochemical evaluation. Results: Clinical improvement was observed in 100% of cases: total clearance in 41 patients (68.3%); partial clearance in 19 patients (32.7%). After treatment, dermoscopic improvement of all non‐pigmented and pigmented AK lesions was observed. Most of the dermoscopic features disappeared with treatment. Total disappearance of specific vascular structures or significant reduction in the number and calibre of new blood vessels was capillaroscopically observed in all patients analysed ( P ≤ 0.001). The immunohistochemical expression of p63 ( P = 0.002), Ki‐67 ( P = 0.015) and VEGF ( P = 0.016) significantly decreased. Conclusions: The clinical efficacy of ingenol mebutate on AKs is confirmed by its effect on angiogenesis, stem cell activity and cell proliferation in vivo .